SISTEM INFORMASI MANAJEMEN STOK DARAH PADA PALANG MERAH INDONESIA KABUPATEN INDRAGIRI HILIR - Ramly Muha Zendra; Muhammad Aidil; Helly Khairuddin (Digital Business Insights Journal, 2025)
Palang Merah Indonesia (PMI) of Indragiri Hilir Regency faces challenges in managing blood stock demand that is often not met due to limited information and manual processes. This study aims to design and develop a web-based information system that can facilitate blood demand management at the Blood Transfusion Unit (UTD) of PMI Indragiri Hilir Regency. This system is designed to replace the blood stock management process that was previously carried out manually through physical letters, into a digital system that is able to accelerate the delivery of information related to blood availability. The system also provides an executive dashboard for monitoring blood stock availability. The system design uses the Unified Modeling Language (UML) and functionality testing is carried out using the Black Box method. The test results show that the system can manage blood stock management well and provide accurate reports.